Pengaruh Kualitas Layanan Dan Digital Marketing Terhadap Kepuasan Pelanggan Menggunakan Erp-Solution Pada Alterra Group - Fernanda, Bella; Agnestia Suhendar, Gilbertha; Andriyani, Silvi (GEMA EKONOMI, 2023)
The purpose of this research is to find out whether service quality (X1) and digital marketing (X2) affect the level of customer satisfaction (Y), and find out whether the two hypotheses (X1 and X2) affect the level of customer satisfaction (Y). The population in this study is all existing clients at Alterra Groupi with a total of 100 people. Sampling in this study using non-probability sampling. The data analysis technique in this study used multiple linear regression analysis. With the results of the research that hypothesis 1 The results of the analysis show that Service Quality has a positive and significant effect on Customer Satisfaction (probability value (sig.) t-count (0.000) < Level of Significant (0.05)), hypothesis 2 The results of the analysis show that Digital Marketing has a positive and significant effect on customer satisfaction (probability value (sig.) t-count (0.006) < Level of Significant (0.05)). And in hypothesis 3 the results of the analysis show that Service Quality and Digital Marketing have a simultaneous effect on Customer Satisfaction (probability value (sig.) t-count (0.000) < Level of Significant (0.05).